2014
DOI: 10.1007/s00520-014-2171-x
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and factors associated with polypharmacy in older people with cancer

Abstract: Polypharmacy is highly prevalent in older people with cancer and associated with impaired physical function and being pre-frail and frail compared to being robust. Research is needed to identify strategies to minimize patients' medication regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
5
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(129 citation statements)
references
References 45 publications
7
115
5
2
Order By: Relevance
“…The cumulative effect of these factors, as illustrated in Figure 1 and previously described by Shenoy et al (13), can be described as a “snowball effect.” The “snowball,” formed of baseline age-related factors is “set in motion” by the cancer diagnosis and is further exacerbated by cancer treatments which cause direct injury to tissues and organs. Polypharmacy and use of potentially inappropriate medications are prevalent in older adults and can exacerbate the toxicity associated with cancer treatments (1416). A multidisciplinary approach, including pharmacist involvement, is vital to preventing polypharmacy and inappropriate medication-related toxicities.…”
Section: Risk Factors Of Cardiotoxicitymentioning
confidence: 99%
“…The cumulative effect of these factors, as illustrated in Figure 1 and previously described by Shenoy et al (13), can be described as a “snowball effect.” The “snowball,” formed of baseline age-related factors is “set in motion” by the cancer diagnosis and is further exacerbated by cancer treatments which cause direct injury to tissues and organs. Polypharmacy and use of potentially inappropriate medications are prevalent in older adults and can exacerbate the toxicity associated with cancer treatments (1416). A multidisciplinary approach, including pharmacist involvement, is vital to preventing polypharmacy and inappropriate medication-related toxicities.…”
Section: Risk Factors Of Cardiotoxicitymentioning
confidence: 99%
“…Polypharmacy is a problem of growing interest given the increase in drug consumption in recent years, particularly among people over the age of 65. Studies indicate that many older adults with cancer are taking more than five medications [2024]. Longer life expectancy, co-morbidity and the implementation of evidence-based clinical practice guidelines in the setting of multi-morbidity all contribute to the presence of polypharmacy [25].…”
Section: Introductionmentioning
confidence: 99%
“…The START/STOPP criteria are effective at identifying PP targets for intervention [6]. These tools have been applied in the primary care, nursing home, and inpatient settings.…”
Section: Advantagesmentioning
confidence: 99%
“…Additionally, both cancer and its treatments often require multiple supportive care medications, which may increase the risk for adverse effects for the older adult. Polypharmacy (PP) is a term with an evolving definition; its definition has been reviewed extensively elsewhere but is commonly described as five or more medications [2][3][4][5][6][7][8]. One study found that 80% of older patients with a recent diagnosis of cancer took more than five medications [6].…”
Section: Introductionmentioning
confidence: 99%